Dampak Biaya Operasional terhadap Profitabilitas Perbankan: Meneliti Efek Moderasi Penerapan Green Banking dan Jenis Bank pada Perbankan Syariah dan Konvensional - Alam, Azhar; Nugroho, Wisnu Adji; Rosyadi, Imron (Universitas Islam Negeri Mataram, 2025)
This study investigates the effect of operational costs on bank profitability in Indonesia, focusing on the moderating roles of green banking practices and bank type (Islamic versus conventional). Using panel data from five Islamic and five conventional banks for 2022–2023, the analysis employs Chow, Hausman, and Lagrange Multiplier tests to determine the most appropriate model, with the Random Effect Model selected for hypothesis testing. The results show that operational costs significantly negatively affect bank profitability, as measured by Return on Assets (ROA), confirming that higher operational costs reduce profitability. While statistically insignificant, the moderating effect of green banking indicates a positive direction, suggesting that adopting green banking can potentially mitigate the negative impact of operational costs on profitability. Furthermore, the interaction between operational costs and bank type reveals that Islamic banks are less sensitive to operational cost increases than conventional banks. However, this moderating effect is also statistically insignificant. These findings highlight the importance of efficient cost management and the strategic adoption of green banking, especially in Islamic banks, to enhance profitability. The study contributes to the literature by providing empirical evidence on the interplay between operational efficiency, sustainability practices, and bank type in the Indonesian banking sector.